Experimental Study on the Effect of Physical Properties of Secondary Refrigerant on the Performance of Indirect Refrigeration Systems in Cold Storage under Different Cooler Combinations - Wang Miantong; Gao Jian; Sun Zhili; Liu Shengchun; Bai Xinmeng; Huang Hongli; Su Chao (Zhileng xuebao)
This study examines the influence of the physical properties of the secondary refrigerant and cooler combinations on the performance of an indirect refrigeration system used in cold storage. An indirect refrigeration system test-bed was built and the performance of two new secondary refrigerants, LM-4 and LM-8, were compared using different coolers to determine the secondary refrigerant with the best performance and the optimal cooler combination. The results demonstrate that the cooling time of the system was affected by the physical properties of the secondary refrigerant and cooler combination. Under the same conditions, the cooling time of the LM-8 system with a finless wall-mounted cooler and a top-mounted fin-tube cooler was the shortest compared with the standalone top-mounted fin-tube cooler and a finless wall-mounted cooler with a finless top-mounted cooler; the cooling time of the LM-8 system is approximately 30.4% less than that of the LM-4 system. The Reynolds numbers corresponding to the optimal working parameters were derived. The optimal refrigeration coefficient of performance (COPr) and comprehensive coefficient of performance (COPc) of the LM-8 system were higher than those of the LM-4 system by 10.7% and 10.9%, respectively. Among the three types of coolers, the total energy consumption of the LM-8 system was 5.8%–13.6%, 2.2%–9.1%, and 3.3%–7.2% lower than that of the LM-4 system. In conclusion, the LM-8 system with a finless wall-mounted cooler and a top-mounted fin-tube cooler is recommended for indirect refrigeration systems in cold storage applications.